Agents driven smart sensors - Zafar, Uzair Ahmed (2017)
Any physical area (like schools, home, hospitals etc.) that uses either mobile devices, sensors, embedded systems or computers to gather information from the users and the environment and eventually, adapt according to the new information gained. [1] Smart spaces compromises of heterogeneous hardware which often leads to the issues of interoperability. One way of reducing the heterogeneity between the sensors is to introduce the semantic interface as sensors default interface. Semantic Web provides a common interface and for-mat for data representation so that one can decrease the heterogeneity of data and increase data reusability. [2] With the Smart Spaces, it is important to use only the hardware’s that can achieve the tasks efficiently and are reliable and durable. When it comes to physical components of Internet of things, there are many different vendors that provide their products and cases often arises where a Smart Space will actually consist of products from different vendors. This is where the need of interoperability comes into story. It plays an important role in integrating the critical services, hardware and applications [3] The aim of this thesis is to present a solution on how that will decrease the heterogeneity among various devices used in these smart spaces and at the same time, present some ex-ample of already existing different architectural workflows that currently exists in real world, that handles the (same) scenario in real world. One of the concept in accomplishing this is presenting every resource with an agent [4]. We discuss on how we can collaborate agents (software/hardware) and sensors to work side by side. The open source JADE framework [5] provides distributed multi agent plat-form where agents can communicate and perform task. We aim on providing the agents with the ability to register sensors, retrieve the information from them and act accordingly if they need to. One framework that provides the platform for registering and using the sensors through the web is 52North [6]. It presents the sensors as a web services interface. This thesis discuss the implementation of a service, which follows semantic web, link and allow the agents in JADE platform to communicate and invoke tasks from the sensors registered in 52North.